PENGARUH METODE LATIHAN SMALL SIDED GAMES TERHADAP KEMAMPUAN PASSING FUTSAL SISWA EKSTRAKURIKULER SMAN 1 PAYAKUMBUH - Rasyid Taqinardi Rilenzulisanto; Naza Putra, Aldo; Gusti Handayani, Sri; Lawanis, Haripah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Small Sided Games training method on the futsal passing ability of extracurricular students at SMAN 1 Payakumbuh. The background of this study is the low passing accuracy shown by the school's futsal players, which requires a more varied training method to improve the skill. This research used a quasi-experimental method with a one group pretest-posttest design, in which a single sample group was measured before and after treatment without a comparison group. The sample consisted of 12 students from grades X and XI who were selected using a purposive sampling technique. Passing ability data were collected through a passing-controlling test and analyzed using descriptive statistics and a Paired Sample t-Test with the help of IBM SPSS Statistics. The results showed that the mean passing score increased from 10.00 in the pretest to 13.33 in the posttest, with a significance value (Sig. 2-tailed) of 0.000 (< 0.05) and a t-value of -10.761. These findings indicate that the Small Sided Games training method has a significant effect on improving the futsal passing ability of extracurricular students at SMAN 1 Payakumbuh, and it can therefore be used as an alternative method for basic futsal skill training. Keywords: Small Sided Games, passing ability, futsal, extracurricular